Pre-mRNA splicing - Nilsen, Timothy (Henry Stewart Talks, 2007)
Recognition of splice junction sequences by components of the spliceosome, Spliceosome assembly, catalysis and disassembly, Roles of snRNPs as well as non-snRNP components, RNA dependent ATPases, Splicing in creating multiple mRNAs
Reviewed at 2015/07/23